Case report: Radiofrequency-induced thermal burn injury in a dog after magnetic resonance imaging - Lichtenauer, Esther A.; Santifort, Koen M.; Bergknut, Niklas; van Soens, Iris; Beukers, Martijn; Carrera, Ines (Frontiers in Veterinary Science, 2024)
A 10-year-old male Shar Pei was referred for lethargy and proprioceptive deficits of the left thoracic limb. An magnetic resonance imaging (MRI) examination of the cervical spinal column and the brain was performed. The MRI examination of the brain was normal. A left-sided C3-C4 intervertebral disc extrusion with spinal cord compression was diagnosed. Medical treatment was elected. Within a week after the MRI examination, the dog presented with deep partial-thickness skin burn wounds in both axillae. Since the specific absorption rate had not exceeded the safety limits during any of the scans and no other procedures or circumstances were identified that could possibly have resulted in burn injuries, the thermal burn injuries were diagnosed as radiofrequency (RF) burns. The wounds healed by secondary intent over the next month. RF burns are the most reported complication in humans undergoing MRI but have not been reported in veterinary patients. Clinicians and technicians should consider the potential risk for RF burns in veterinary patients and take precautions regarding positioning of the patient and take notice of any signs of burn injury when performing follow-up examinations.